GRAMMATICAL CHALLENGES IN TRANSLATING WAYANG ORANG SCRIPTS: A CASE STUDY ON OMISSION AND MISFORMATION ERRORS - Setiawan Putra, Joshua Levi; Sumardiono, Sumardiono (English Education Department Slamet Riyadi University Surakarta, 2024)
This study examines grammatical errors in the translated scripts of Wayang Orang Sriwedari by MBKM Matching Fund students at Universitas Slamet Riyadi Surakarta. Using Dulay et al.’s (1982) Surface Strategy Taxonomy, the analysis focuses on Omission and Misformation errors, which frequently occur in the texts. Omission errors (54 cases) involve missing auxiliary verbs and prepositions, while Misformation errors (52 instances) result from incorrect verb forms and article usage, affecting readability and coherence. By applying content analysis (Miles & Huberman, 1994), this study investigates the causes of these errors, including first-language interference, grammatical unawareness, and overgeneralization of rules. The findings highlight the need for improved translation strategies to enhance grammatical accuracy and text clarity. Keywords: Translation, Error Analysis, Grammatical Error